Keabsahan Perjanjian Restrukturisasi Nomor: 003/Pam/F/K.KH/III/2018 Oleh Dan Antara Perusahaan Daerah Air Minum Daerah Ibukota Jakarta (PAM Jaya) Dan PT. Aetra Air JakartaBerdasarkan Putusan MK Nomor 85/PUU-IX/2013 - Nada Najiha; Ria Safitri; Fathudin Fathudin (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2020)
The main problem in this research is regarding the management of water resources after the Constitutional Court Decision Number 85 / PUU-IX / 2013 and whether or not the Restructuring Agreement Number 003 / PAM / F / K.KH / III / 2018 between PAM Jaya and PT. Aetra Air Jakarta based on the Constitutional Court Decision Number 85 / PUU-IX / 2013. This research aims to make everyone understand that the contents of the agreement must be in accordance with the prevailing laws and regulations. This research method uses a normative juridical approach. Juridical normative in this study has two sources of law, namely primary and secondary sources of law. Primary sources of law refer to the Restructuring Agreement Number 003 / PAM / F / K.KH / III / 2018 and the Constitutional Court Decision Number 85 / PUU-IX / 2013. The results of the study show that in the Constitutional Court Decision Number 85 / PUU-IX / 2013 mandating the participation of state shares in water resources management cooperation with the private sector, while the Restructuring Agreement Number 003 / PAM / F / K.KH / III / 2018 is considered invalid. valid because it does not include state shares in accordance with the appropriate proportion.